Optimalisasi Inventory Planning dan Proses Pengadaan untuk Meningkatkan Efisiensi Distribusi di PT Salam Jaya Lestari - Yuwono, Wisnu; Angelin, Angelin (Mestaka: Jurnal Pengabdian Kepada Masyarakat, 2026)
This Community Engagement Program was conducted at PT Salam Jaya Lestari, focusing on optimizing inventory planning and procurement processes to improve the company’s distribution efficiency. The topic was selected based on the company’s operational challenges, including fluctuations in customer demand, the risk of stock discrepancies, delivery delays, and procurement document management that had not yet been optimally organized. The objective of this program was to improve the accuracy of inventory planning, enhance procurement processes, and support smoother distribution through workflow improvements within the Planner & Buyer Division. The implementation method involved direct observation and active participation in daily work activities, including stock checking, preparation and verification of Purchase Orders, procurement document management, and coordination with suppliers and logistics partners. The results show improved efficiency in stock-checking processes, more structured procurement activities, and a reduced risk of stock discrepancies and distribution delays. The program outcomes have helped the company manage inventory and procurement processes in a more structured and efficient manner.